THE USE OF LANGUAGE STYLE ON THE VICTORY SPEECH OF DONALD TRUMP AND JOE BIDEN - Putri Plorensia Panggabean; Sondang Manik; Rony Arahta Sembiring (Jurnal Scientia, 2022)
Abstract This study focuses on the use of Language Style in Donald Trump and Joe Biden's victory speeches and what type of Language Style is dominant in their respective speeches. The research data was collected from the internet. This research uses a qualitative approach. In analyzing the data, this study uses Martin Jooz's (1967) Theory; Frozen Style, Formal Style, Casual Style, Consultative Style and Intimate Style. This study found 50 detected data entered into the Type of Language Style in Donald Trump's speech, namely 27 Formal Style, 13 Casual Style and 10 intimate style. And the researcher also found 50 data that entered into the type of Language Style in Joe Biden's speech, namely 36 Formal Style, 11 Casual Style, 2 Frozen Style and 1 Intimate Style. It can be concluded that Donald Trump and Joe Biden use more Formal Language Style because they speak in serious situations and in a formal place. Meannwhile, they occasionally use other types of Language Style to make listeners interested and understand the message conveyed.AbstractThis study focuses on the use of Language Style in Donald Trump and Joe Biden's victory speeches and what type of Language Style is dominant in their respective speeches. The research data was collected from the internet. This research uses a qualitative approach. In analyzing the data, this study uses Martin Jooz's (1967) Theory; Frozen Style, Formal Style, Casual Style, Consultative Style and Intimate Style. This study found 50 detected data entered into the Type of Language Style in Donald Trump's speech, namely 27 Formal Style, 13 Casual Style and 10 intimate style. And the researcher also found 50 data that entered into the type of Language Style in Joe Biden's speech, namely 36 Formal Style, 11 Casual Style, 2 Frozen Style and 1 Intimate Style. It can be concluded that Donald Trump and Joe Biden use more Formal Language Style because they speak in serious situations and in a formal place. Meannwhile, they occasionally use other types of Language Style to make listeners interested and understand the message conveyed.